Assessing the nutrition knowledge, beliefs, and behaviors of food pantry managers: implications for healthier food environments - Sanchez, Sofia O.; Funderburk, Katie; Reznicek, Erin; Bubb, Robert R.; Frugé, Andrew D.; Duke-Marks, Adrienne; Hinnant, J. Benjamin; Parmer, Sondra M. (Frontiers in Public Health, 2025)
IntroductionFood pantry managers play a key role in determining the food environment of the pantry, which can influence their clients’ dietary composition. However, their impact on pantry food environments remains understudied. We sought to understand food pantry managers’ nutrition knowledge, beliefs, and behaviors (KBBs) in this study.MethodsWe surveyed 47 Alabama food pantry managers’ nutrition KBBs from November 2022 to November 2023. Validated and previously published tools used include the Consumer Nutrition Knowledge Scale, a diet beliefs scale, and a dietary-related consumer behavior questionnaire.ResultsThe majority of managers were college-educated (54%), white (74%), and female (74%), with a mean age of 60 ± 13 years and an average of 7 ± 5.5 years of experience in managing food pantries. Managers reported positive nutrition beliefs and behaviors but scored lower on objective nutrition knowledge. Exploratory analyses indicated moderate to very strong associations between KBBs, pantry characteristics, and neighborhood characteristics.ConclusionNutrition education for pantry managers, along with improved pantry infrastructural support, could play a key role in improving the healthfulness of the food provided.